Criminalisation of politics - Beyond Vohra Committee report - Dubhashi, P.R. (2002)
Criminalisation of politics has emerged as a new threat for the already delicate social fabric of the country. Mafia dons, gang leaders and history sheeters have found it convenient to pose as champions of their caste, community or the down-trodden. Riding on this wave of popularity among gullible and illiterate voters they have set their eyes on Parliament and state legislators. The article analyses this dangerous phenomenon and suggests some hard measures to keep such elements under check. - Reproduced.
Keywords: Vohra Committee Report; India - Politics and government; Politics and government